2015
DOI: 10.1002/wmh3.152
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Insecurity is Associated with Heterogeneous Patterns of Diet Quality Across Urban and Rural Regions of Malawi

Abstract: The nutritional consequences of food insecurity in rural as compared to urban regions of low‐ and middle‐income countries (LMICs) have not been well differentiated. We aimed to determine the region‐specific associations of food security with diet diversity, consumption of foods associated with the nutrition transition, and child stunting and overweight. We used data on 12,271 households from the 2010–2011 Malawi Third Integrated Household Survey (IHS3). We used multiple logistic regression analyses to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…A number of studies in Malawi have also shown that young children’s complementary foods are inadequate in energy density, protein and micronutrients required for child nutrition [11]. As well, low dietary diversity, food insecurity, inadequate number of feedings in a day, low levels of exclusive breastfeeding and seasonal fluctuations in food prices are some of the persistent reasons for higher rates of child undernutrition in Malawi [12, 13]. The majority of Malawians are rural, smallholder farmers who rely on their own food production for their consumption, and experience ongoing challenges with low and declining soil fertility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies in Malawi have also shown that young children’s complementary foods are inadequate in energy density, protein and micronutrients required for child nutrition [11]. As well, low dietary diversity, food insecurity, inadequate number of feedings in a day, low levels of exclusive breastfeeding and seasonal fluctuations in food prices are some of the persistent reasons for higher rates of child undernutrition in Malawi [12, 13]. The majority of Malawians are rural, smallholder farmers who rely on their own food production for their consumption, and experience ongoing challenges with low and declining soil fertility.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of Malawians are rural, smallholder farmers who rely on their own food production for their consumption, and experience ongoing challenges with low and declining soil fertility. Malawi has high rates of rural poverty, and chronic seasonal food insecurity is commonly experienced [10, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…Authors of the reviewed articles attempted to deal with the limitations by using complex statistical methods to account for error and bias. Ordinary least-squares regression analysis was commonly used and compared with other types such as quantile regression (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) .…”
Section: Resultsmentioning
confidence: 99%
“…food secure or food insecure) (23,26,27,30,(33)(34)(35)(36)(37) , three studies used a ranking in the range of 1, 2 or 3 (i.e. food secure, moderately food insecure, severely food insecure) (22,28,38) and five studies assessed the variables as continuous measures (21,24,25,28,29) . Five studies also explored food security qualitatively, where coping strategies and participant experiences were assessed (21,24,25,30,41) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation